2019
DOI: 10.1159/000501212
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Follow-Up of Unaffected Fellow Eyes in Patients with Polypoidal Choroidal Vasculopathy

Abstract: Purpose: To evaluate the incidence and risk factors of neovascular age-related macular degeneration (nAMD) including polypoidal choroidal vasculopathy (PCV) or any type of choroidal neovascularization (CNV) in fellow eyes of unilateral PCV. Methods: This retrospective study included 48 patients with unilateral PCV. For the initial PCV diagnosis, optical coherence tomography and indocyanine green angiography were performed, and patients with and without neovascularization were compared. Results: Of 48 fellow ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Previous studies on fellow eyes of PCV reported that PCV could develop in 9% to 17% of fellow eyes after long-term follow-up [ 16 , 17 ]. A few studies have reported on precursor lesions of PCV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on fellow eyes of PCV reported that PCV could develop in 9% to 17% of fellow eyes after long-term follow-up [ 16 , 17 ]. A few studies have reported on precursor lesions of PCV.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have reported on precursor lesions of PCV. Kang et al reported drusen-like deposits and pigmentary changes in contralateral eyes of PCV [ 18 ]; Kim et al reported fellow eyes of PCV that developed PCV or CNV during follow-up presented more irregular RPE elevation, branching vascular network, thicker choroid, choroidal vascular dilation and CVH [ 16 ]; Baek et al reported RPE and outer retinal abnormalities accompanied by pachyvessel increased risk of neovascularization development for fellow eyes of PCV [ 17 ]. These reports were consistent with our reports where RPE abnormalities could be precursor lesions of PCV, although previous studies focused more on contralateral eyes of unilateral PCV, while our case series reviewed the study eyes in the context of pachychoroid spectrum diseases, showing that PPE lesions could progress to PCV after long-term follow-up, providing evidence that PPE could be precursor lesions of PCV and that pachychoroid spectrum diseases could be a continuous disease process.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 48 fellow eyes, the development of either nAMD or PCV was observed in 8 eyes (17%). SFCT, irregular RPE elevation, choroidal vascular dilation, choroidal vascular hyperpermeability (CVH), and the presence of branching neovascular network (BNN) in the fellow eyes were significantly correlated with the development of PCV 43…”
Section: Updates On Risk Factors and Biomarkers For Pcv Developmentmentioning
confidence: 99%
“…CNV occurs in 9% of fellow eyes in individuals with unilateral PCV or aneurysmal type 1 neovascularization, usually retinal pigment epithelium and outer retinal abnormalities with pachy vessels (30). A study that followed patients with unilateral PCV and CNV for up to 5 years found that 17% of fellow eyes developed PCV or CNV (31).…”
Section: Quadrant N (%) -mentioning
confidence: 99%